ASSESSMENT OF ENVIRONMENTAL IMPLICATION OF OIL EXPLORATION IN AKKO LOCAL GOVERNMENT AREA GOMBE STATE, NIGERIA - Ali Mahmoud, Hassan; Umar Shinga, Khalid (FUDMA Journal of Sciences, 2026)
Harnessing and exploration of natural resources has become critical in stimulating socio-economic and technological development since industrial revolution, although with all its countless benefits, it also has some numerous environmental impacts that trigger global environmental menace. Therefore, the study assessed the environmental implication of oil exploration in Akko Local Government Area, Gombe State, Nigeria. A multi-stage sampling technique was used in selecting 384 respondents. Data was collected using structure questionnaire, key informant interview (KII) and focus group discussion (FGD). The data was analyzed using statistical tool (SPSS Version 20) and Geographic information system software. findings of the study revealed that, the satellite imagery of land use/land cover of the study area indicated clear changes especially places that were covered by vegetation before, are now occupied by buildings and road constructions and that attests and confirmed commencement of extraction of crude oil in the study area as confirmed by 37.5% of the respondents. Additionally, the study revealed that (79.7%) of the respondents were aware of the oil and gas exploration activities impact negatively on the environment. About 52.9%, 49.2% and 39.8% of the respondents perceived an increase in land crisis, worsen environmental pollution, health concerns, loss of livelihood and conflict of interest, may be the order of the day as their negative expectations respectively. Therefore, the study concluded that oil exploration has impacted negatively in the environment and the ecosystem